Sosialisasi “Perlindungan Hukum Bagi Guru Dalam Mendisiplinkan Siswa” di SDN Jatimulya 11, Tambun Selatan, Kabupaten Bekasi - Nining Yurista Prawitasari; Akbar Sayudi; Gina Asri Ruwaida (LPPI UMN AL WASHLIYAH, 2024)
This research focuses on how the law protects teachers from criminalization. Legal protection for teachers is the government's effort to protect teachers and other education personnel in carrying out their professional duties. The research method used is normative juridical, which is legal protection for teachers related to criminal acts of violence in the educational process as regulated in Law Number 14 of 2005 and Government Regulation Number No. 19 of 2017, amendments to Government Regulation Number 74 of 2008. There are differences in perceptions from parents and schools, especially teachers as educators, namely punishments that have a deterrent effect such as pinching, twisting, hair cutting and other disciplinary actions have been considered human rights violations based on Child Protection Law according to parents' perceptions. Meanwhile, teachers still consider these sanctions to be in the educational category for disciplining students. Legal outreach to teachers is very important to equip teachers to understand the law and raise legal awareness.